Management of the Receipt Issuance Menu in the Indonesian Auction Application for Public Services at the State Wealth and Auction Service Office (KPKNL) of the DJKN Suluttenggomalut Region - Andhi Rifqi Mubarok; Muhammad Nur Abdi (International Journal of Asian Business and Management, 2023)
This study aims to, (1) test the effect of issuing auction repayment receipts on the Indonesian auction application on public services, (2) test the effectiveness of using the menu receipt of auction settlement in the Indonesian auction application at Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) in the area of the Direktorat Jenderal Kekayaan Negara (DJKN) of North Sulawesi, and (3) test the ease of use of the menu for issuing auction repayment receipts on the Indonesian auction application on the speed and accuracy of public services. The data collection technique used in this study is a qualitative descriptive method with interview techniques to respondents who are directly responsible for using the receipt issuance menu feature in the Indonesian auction application. Respondents who were interviewed were from 3 (Three) KPKNL in the DJKN region of North Sulawesi, namely (1) KPKNL Gorontalo, (2) KPKNL Palu, and (3) KPKNL Ternate. The results of this study indicate that the use of the auction repayment receipt menu in the Indonesian auction application has been effectively used since the Regulation of the Direktur Jenderal Kekayaan Negara (DJKN) Number 02/KN/2022 concerning Auction Administration Guidelines at the KPKNL. Other results from this study indicate that the menu for issuing auction repayment receipts in the Indonesian auction application is able to provide services to the community, especially related to auction repayment receipts, more quickly and precisely. However, from the results of these achievements there are still deficiencies that need to be refined to the contents of the menu features of the research object